2009
DOI: 10.1158/0008-5472.can-08-4750
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of CXCR4 and CD62L in Chronic Lymphocytic Leukemia Cells Is Triggered by B-Cell Receptor Ligation and Associated with Progressive Disease

Abstract: Progressive cases of B-cell chronic lymphocytic leukemia (CLL) are frequently associated with lymphadenopathy, highlighting a critical role for signals emanating from the tumor environment in the accumulation of malignant B cells. We investigated on CLL cells from 30 untreated patients the consequence of B-cell receptor (BCR) triggering on the membrane expression of CXCR4 and CD62L, two surface molecules involved in trafficking and exit of B-lymphocytes from lymph nodes. BCR stimulation promoted a strictly sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
61
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 42 publications
(56 reference statements)
13
61
0
Order By: Relevance
“…19 The prominence of factors related to proliferation is in line with the key role of BCR signaling capacity and microenvironment in disease progression. 6,20 As the 4 prognostic factors had independent prognostic weight, we combined these unfavorable factors. The cohort was split into 5 groups according to the number of unfavorable prognostic factors they exhibited.…”
Section: Resultsmentioning
confidence: 99%
“…19 The prominence of factors related to proliferation is in line with the key role of BCR signaling capacity and microenvironment in disease progression. 6,20 As the 4 prognostic factors had independent prognostic weight, we combined these unfavorable factors. The cohort was split into 5 groups according to the number of unfavorable prognostic factors they exhibited.…”
Section: Resultsmentioning
confidence: 99%
“…26 These in vivo data indicate that CLL subclones with lower blood CXCR4 surface levels are a fraction of cells that has recently exited the tissues into the blood. BCR signaling results in the down-modulation of CXCR4, 17,27 along with enhanced chemotaxis toward CXCL12 and CXCL13. 17 This may explain why ZAP-70 ϩ CLL cells display increased chemotaxis and survival in response to CXCL12 compared with ZAP-70 Ϫ CLL cells, 28 given that ZAP-70 expression is associated with a higher responsiveness to BCR stimulation.…”
Section: T Lymphocytesmentioning
confidence: 99%
“…Interestingly, several CLL cells evade apoptosis in vitro through an enhanced survival response after BCR stimulation. 6,7,9,10 After BCR triggering, which is mediated by antigen binding to cell surface Igs, prolonged activation of the MEK-ERK and PI3K-AKT pathways, as well as efficient degradation of I]kappa]B and activation of NF-B have been associated with the induction of antiapoptotic and survival signals. [11][12][13] These molecular events lead to important changes in gene transcription and subsequent B-cell fate specification.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable amounts of data have shown that antigen-driven signals are involved in the pathogenesis and progression of CLL malignancies. [6][7][8][9] Although CLL cells accumulate and are resistant to cell death in vivo, they rapidly become apoptotic during in vitro culture. Interestingly, several CLL cells evade apoptosis in vitro through an enhanced survival response after BCR stimulation.…”
Section: Introductionmentioning
confidence: 99%